PENGEMBANGAN SISTEM INFORMASI MANAJEMEN BIMBINGAN SKRIPSI MAHASISWA IKIP PGRI PONTIANAK - Ramadhani, Dochi; Sulistiyarini, Dewi; Sabirin, Febrianto; Hadiyan, Dimas (LPPM IKIP PGRI Pontianak, 2023)
Thesis is a scientific work that is a requirement for obtaining a Bachelor's degree. Thesis guidance is an important part of completing the thesis so a system is needed that can facilitate student thesis guidance at the Information Technology Education Program (P.TI), IKIP PGRI Pontianak. Management Information System of Student Thesis Guidance (SIMBISA) was developed using the ADDIE model. The instruments used were interviews, documentation, and questionnaires. The subjects in the study consisted of 2 system experts and 20 prospective system users. Test results by system experts show that SIMBISA is feasible to use and gets a very good response from potential users so that it can be implemented in the P.TI IKIP PGRI Pontianak.